Microsoft Azure Security Technology (AZ-500) Cert Prep by Microsoft Press. - Warner, Tim; Press, Microsoft (linkedin.com, 2024)
Learn the skills you need to master to tackle the Microsoft Azure Security Technologies (AZ-500) certification exam.